Incorporation of NGR1 promotes bone regeneration of injectable HA/nHAp hydrogels by anti-inflammation regulation via a MAPK/ERK signaling pathway - Liu, Yi; Zhang, Yifan; Zheng, Zexiang; Zhong, Wenchao; Wang, Haiyang; Lin, Zhen; Li, Lihua; Wu, Gang (Frontiers in Bioengineering and Biotechnology, 2022)
Suitable bone grafts are commonly required to achieve successful bone regeneration, wherein much effort has been spent to optimize their osteogenesis. Increasing evidence has demonstrated that reducing the levels of TNF-α can enhance bone regeneration at the injury site. Notoginsenoside R1 (NGR1) has been extensively studied in the field of anti-inflammation and regenerative medicine. Nanosized hydroxyapatite (nHAp) possesses excellent biocompatibility and osteoconductivity. In this study, we fabricated a thermoresponsive, injectable hyaluronic acid/nHAp (HA/nHAp) composite hydrogel incorporated with NGR1 to promote bone regeneration. Furthermore, NGR1-HA/nHAp hydrogel could enhance bone regeneration than those of HA and HA/nHAp hydrogels, profited by the underlying osteoblastic mechanism that NGR1 could facilitate activation of the MAPK/ERK signaling pathway and down-regulate the expression of TNF-α, ultimately upregulated expression of osteogenic genes. In summary, the NGR1-HA/nHAp composite hydrogel with controlled inflammation, and excellent osteogenic effect, will have great potential for use in bone regeneration applications.